Conditions of community socio-economic activities in the Lappa Fisihing Landing Base Area, Sinjai District - Hamjan, Dewi Febriani (Politeknik Negeri Sambas, 2024)
The Lappa Fish Landing Base located in Sinjai Regency is a type D fishing port that operates daily. The fishing port not only performs fish landing activities but the existence of PPI Lappa Sinjai is known for its various socio-economic activities and is one of the centers of economic circulation in Sinjai. The research aims to find out the socio-economic activities of the community in the PPI Lappa Sinjai Area, to find out how much PPI Lappa contributes to fishermen and the community around the PPI Lappa fishing port, and to find out how the community's socio-economic activities have changed with the existence of the PPI Lappa. A qualitative research method using a descriptive-analytical approach was used. Data collection was conducted using interviews, observations, and documentation. Data analysis techniques included data collection, data reduction, data presentation, and drawing conclusions or verification. This research provides an overview of the socio-economic activities of the community in the PPI Lappa area, Sinjai, which is dominated by production, processing, and marketing activities. PPI Lappa contributes to increasing employment and marketing activities by processing businesses, the UMKM, and tourism. The community makes efforts to use responsible fishing ports to support the socio-economic sustainability of fishing ports.